Design and Characteristic Analysis of a Novel Compact Torsion Spring for Assistive Exoskeleton Robots - Mingxing Yang; Taohong Jia; Yue Yang; Shiliang Liu; Tao Zhou (IEEE Access)
To improve traditional rigid exoskeletons in terms of human-machine interaction flexibility and safety, a novel compact torsion spring was developed for lower limb joint assistance in this study. The flexibility of the torsion spring drive was enhanced by the deformation of elastic elements between inner and outer rings and three limiting beams were added between elastic bodies to improve its intensity. Subsequently, the overall quality, maximum stress, and maximum deformation were selected as optimization objectives and the size of the torsion spring was optimized with finite element method. To verify the stable stiffness characteristics of the design scheme under different load conditions, finite element simulation and experimental data were respectively utilized to fit the torque and torsion angle variables in MATLAB. Finally, a performance testing experimental platform for the torsion spring was established to experimentally analyze its stiffness characteristics and position tracking performance. The feasibility of the torsion spring was confirmed through experiments on exoskeleton following human walking.